Experimental study of the influence of gradation on the dynamic properties of centerline tailings sand. Issue 151 (December 2021) - Huang, Xin; Cai, Xiaoguang; Bo, Jingshan; Li, Sihan; Qi, Wenhao
Abstract: Gradation is an important factor that affects the dynamic characteristics of tailings by the centerline method. For underflow tailings and overflow tailings under different grading effects of the cyclone, resonant column tests of saturated and unsaturated samples of different graded tailings sands are performed under the design dry density and isotropic consolidation conditions to analyse the influence of the gradation characteristics on the dynamic shear modulus and damping ratio of tailings sand. The test results show that under different grading conditions, the maximum dynamic shear modulus gradually increases, and the maximum damping ratio gradually decreases with increasing fine particle content of underflow tailings sand; meanwhile, the maximum dynamic shear modulus of overflow tailings sand gradually decreases, and the maximum damping ratio gradually increases with increasing fine particle content of overflow tailings sand. In underflow tailings sand, coarse particles (diameter >0.075 mm) act as the skeleton, and fine particles (diameter <0.075 mm) can fill the gaps among the coarse particles. When the content of fine particles in underflow tailings sand increases, the dynamic shear modulus increases, and the damping ratio decreases with the gradual increase in the fine particle content of the overflow tailings sand, the effective contact area among the coarse particle skeletons decreases, and the connection effect decreases; hence, the dynamic shear modulus decreases, and the damping ratio increases. The results of this research can provide basic data for the dynamic response analysis of tailings sand of different grades and a reference for the design and management of centerline method tailings ponds in areas with high seismic intensity. Highlights: The effect of the gradation on the dynamic shear modulus and damping ratio of the centerline tailings sand is explained. The Hardin-Drnevich model parameters were regression-fitted and compared with the general sand curves suggested by Seed. The dynamic shear modulus and damping ratio datas of saturated tailings sand and unsaturated tailings sand in the centerline method under different gradations are obtained.